Power at work [ how employees reproduce the corporate machine - McCabe, Darren (Routledge research in employment relations ;, 2007)
Providing insights into working life, this book offers an approach to innovation in the work place. It argues that many innovations associated with the corporation seem to reproduce many of the conditions that we associate with the industrial age. It demonstrates the debilitating consequences of these interventions